Lipophilic indocarbocyanine conjugates for efficient incorporation of enzymes, antibodies and small molecules into biological membranes. (April 2018) - Smith, Weston J.; Tran, Huy; Griffin, James I.; Jones, Jessica; Vu, Vivian P.; Nilewski, Lizanne; Gianneschi, Nathan; Simberg, Dmitri
Abstract: Decoration of cell membranes with biomolecules, targeting ligands and imaging agents is an emerging strategy to improve functionality of cell-based therapies. Compared to covalent chemistry or genetic expression on the cell surface, lipid painting (i.e., incorporation of lipid-conjugated molecules into the cell bilayer) is a fast, non-damaging and less expensive approach. Previous studies demonstrated excellent incorporation and retention of distearyl indocarbocyanine dye DiI in membranes of cells in vitro and in vivo . In order to exploit the membrane stability of DiI, we synthesized an amino-DiI derivative, to which we subsequently conjugated an antibody (cetuximab), an enzyme (superoxide dismutase), and a small molecule (DyLight 800). Red blood cells have long been used as drug delivery vehicles so they were utilized as a model to study the incorporation of DiI conjugates in the plasma membrane. All the DiI constructs demonstrated fast and efficient ex vivo incorporation in the membrane of mouse RBCs, resulting in millions of exogenous molecules per RBC. Following an intravenous injection into mice, the molecules were detected on circulating RBCs for several days. DiI anchored molecules showed longer residence time in blood and significantly higher area under the curve (AUC) compared to free non-conjugated molecules. Thus, cetuximab, SOD and DyLight painted on RBC showed 5.5-fold, 6.5-fold and 78-fold increase in the AUC, respectively, compared to the non-modified molecules. Lipophilic indocarbocyanine anchors are a promising technology for incorporation of biomolecules and small molecules into biological membranes for in vivo applications.